2022
DOI: 10.3390/ijerph19158968
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and Attempted Suicide in Poland before and during the COVID-19 Pandemic between 2019 and 2021

Abstract: The COVID-19 pandemic is related to changes in rates of suicide and suicide attempts in many countries, and some differences have been observed regarding the prevalence of suicidal behaviours in different age and gender groups. The aim of this study is to analyse the number of suicides and suicide attempts per 100,000 people between 2019 and 2021 in Poland. Using police and government data on suicide and suicide attempts in Poland, three age categories were investigated: 13–24 years old, 25–65 years old, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 30 publications
2
8
0
Order By: Relevance
“…A total of 8642 studies were screened, with 72 studies (131 samples) meeting the inclusion criteria. Among them, 16 [ 10 , 11 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ], 11 [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ], and 19 [ 8 , 13 , 14 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ] only addressed changes in suicidal ideation, suicide attempt, and death by suicide, respectively; 25 [ 9 , 12 , 15 , 16 , 92 , 93 , 94 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 8642 studies were screened, with 72 studies (131 samples) meeting the inclusion criteria. Among them, 16 [ 10 , 11 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ], 11 [ 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 ], and 19 [ 8 , 13 , 14 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ] only addressed changes in suicidal ideation, suicide attempt, and death by suicide, respectively; 25 [ 9 , 12 , 15 , 16 , 92 , 93 , 94 , …”
Section: Resultsmentioning
confidence: 99%
“…There were 37 studies with 55 samples (30 non-clinical and 25 clinical samples, respectively) included for the analysis of suicidal ideation. Specifically, several studies contributed more than one sample due to multiple peri-pandemic data collection [ 9 , 65 , 70 , 75 , 106 , 108 ] or subsets of participants [ 75 , 103 , 111 ]. With an average risk of bias score of 7.5 (range = 4–9), the majority of included studies had adequate size and information for their sample, and they employed appropriate sampling and statistical methods.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the results of a study in high and upper‐middle‐income countries, the number of suicides in the early months of the Covid‐19 pandemic was unchanged or decreased compared to the period before the pandemic 12 . In contrast, some studies shown through the covid‐19 epidemic have described higher rates of suicide in various nations, such as India, 3,13 Poland, 14 Bangladesh, 15 and Norway 16 . Nevertheless, social, health, political, cultural, and economic scenarios differ from country to country 11 .…”
Section: Introductionmentioning
confidence: 99%
“…Several international studies have validated the impact of the COVID-19 pandemic on risks to mental well-being. The pandemic’s daily life has also contributed to a decline in mood among Poles ( Stańdo et al, 2022 ). Spirituality and religion can be a positive reassurance in societies facing epidemics and a help in times of crisis ( Fardin, 2020 ).…”
Section: Introductionmentioning
confidence: 99%